2010
DOI: 10.1016/s1976-1317(10)60002-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hearing Protection Behavior Among Power Plant Workers

Abstract: Social modeling and perceived benefits of using the HPDs are important for workers to keep minimal or certain level of using the HPDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 11 publications
1
14
0
5
Order By: Relevance
“…[4] Several factors are reported to influence the wearing of hearing protection: Health beliefs, perceived risk, perceived probability of risk, perceived benefits, and comfort of wearing the device. [5][6][7][8] New Zealand data suggest that a high proportion of hearing loss claims come from the manufacturing sector and plant and machine operators. [2] Previous New Zealand research into of occupational exposure found that just half the plant and machine operators, assemblers, and elementary workers who worked in noisy environments reported hearing protection use.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Several factors are reported to influence the wearing of hearing protection: Health beliefs, perceived risk, perceived probability of risk, perceived benefits, and comfort of wearing the device. [5][6][7][8] New Zealand data suggest that a high proportion of hearing loss claims come from the manufacturing sector and plant and machine operators. [2] Previous New Zealand research into of occupational exposure found that just half the plant and machine operators, assemblers, and elementary workers who worked in noisy environments reported hearing protection use.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to increase the awareness of workers by allowing them to self-perceive the risk of noise in their working environment. This is due to previous studies which showed that workers were reluctant to wear hearing protection devices (HPD) regularly and there was a low utilisation rate of hearing protection in workplaces [ 86 , 87 ]. The main reasons workers disregarded the protective function of HPD was that they could not self-perceive the risks of noise and had low self-efficacy in HPD use [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Power plants are among the noisiest workplaces, with a large number of workers exposed to noise levels between 80-90 dB, according to routine noise monitoring [5]. Within such plants, major sources of noise include steam turbine generators (STG), combustion inlet filter house, and the exhaust stack or heat recovery steam generator (HRSG).…”
Section: Applied Environmental Researchmentioning
confidence: 99%